Lowly or Negative Benchmark Rates Bandwagon: Any Risk Implications for Islamic banks? - Chattha, Jamshaid Anwar; Alhabshi, Syed Musa (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2018)
To stimulate the economy, regulators across all jurisdictions have been taking unconventional approaches. Thus, in recent years, the management of benchmark rates (or interest rates) has received considerable prominence in the banking sector due to some reasons including supervision banks' benchmark rates under Basel II. This paper reviews the possible dysfunctional implications of lowly and/or negative rates and provides a risk management and regulatory perspective for Islamic banks. These consequences call for a better risk management with appropriate tools and effective supervisory oversight. It hoped that the initial discussion presented in this paper on the implications and controls invites a broader debate on this issue in the Islamic financial services industry. DOI: 10.15408/aiq.v10i1.6121